The Role of Physical Activity in Diabetes Management: Benefits, Risks, and Recommendations - review - Dądela, Bartosz; Gnitecki, Szymon; Jasińska, Joanna; Janczura, Szymon; Majewska, Emilia; Śliwa, Natalia; Markowski, Marcin; Zielonka, Kacper; Kawalska, Eliza; Borowski, Maciej (Quality in Sport, 2025)
Regular physical activity plays a key role in managing type 1 (T1D) and type 2 diabetes (T2D), improving insulin sensitivity, glycemic control, and metabolic health. Exercise helps maintain a healthy body weight, reduces the risk of cardiovascular diseases, and enhances mental well-being. For individuals with T2D, physical activity decreases insulin resistance, while for those with T1D, it increases the risk of hypoglycemia, requiring adjustments in insulin doses and carbohydrate intake. Continuous glucose monitoring (CGM) systems facilitate the detection of hypoglycemia, especially at night. A combination of aerobic and resistance training is recommended for optimal glycemic control and HbA1c reduction. In individuals at risk of T2D, such as those with prediabetes, regular exercise can delay or prevent disease onset. Tailored exercise programs and education on glucose management are essential for safe and effective implementation. Future research should focus on individualized exercise plans and long-term effects of physical activity on diabetes progression and complications. In conclusion, integrating regular physical activity into diabetes management significantly improves health outcomes and quality of life for patients with T1D and T2D, though challenges like hypoglycemia must be carefully managed.